1996
DOI: 10.1017/s0890037x0004584x
|View full text |Cite
|
Sign up to set email alerts
|

Carryover Potential of Pyrithiobac to Rotational Crops on a Mississippi Black Belt Region Clay Soil

Abstract: Field studies were conducted on a Black Belt region clay soil to evaluate pyrithiobac injury to cotton and potential carryover to grain sorghum, soybean, and wheat. Pyrithiobac was applied PPI, PRE, POST at pinhead square, or POST at first bloom at rates of 70, 140, or 280 g ai/ha to cotton. Cotton injury was 7% or less at all rates and application timings. Cotton yield was not reduced by any treatment. The PRE application to cotton, averaged over rates, reduced yield of wheat planted in the fall compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
3
9
0
1
Order By: Relevance
“…The similar field persistence recorded in loam and clay loam soils is in agreement with the results of Johnson et al (1993), Jordan et al (1993b), and Webster and Shaw (1996). Furthermore, the increased field persistence of pyrithiobac with increasing application rate agrees with the results of Jordan et al (1993b) and Webster and Shaw (1996).…”
Section: Pyrithiobac Field Persistencesupporting
confidence: 88%
See 2 more Smart Citations
“…The similar field persistence recorded in loam and clay loam soils is in agreement with the results of Johnson et al (1993), Jordan et al (1993b), and Webster and Shaw (1996). Furthermore, the increased field persistence of pyrithiobac with increasing application rate agrees with the results of Jordan et al (1993b) and Webster and Shaw (1996).…”
Section: Pyrithiobac Field Persistencesupporting
confidence: 88%
“…Shorter persistence in wet and warm soils than in dry and cool soils was reported for other ALS-inhibiting herbicides (Hultgren et al 2002;James et al 1999). However, the similar pyrithiobac persistence when applied PRE and PPI in all soils is in contrast to the results of Webster and Shaw (1996), who found longer field persistence when pyrithiobac was applied PPI than PRE or POST.…”
Section: Pyrithiobac Field Persistencementioning
confidence: 62%
See 1 more Smart Citation
“…Rafii and Ashton (1979) observed in a greenhouse trial that soybean treated with a 1/8×rate of fluridone had reduced shoot length and weight, severe chlorosis, and inhibition of trifoliate formation. Webster and Shaw (1996) also reported that pyrithiobac applied at 140 g ha −1 PPI reduced soybean yield the following year. Based on their results and the results of this experiment, it is likely that pyrithiobac would affect small-seeded broadleaf cover crop establishment in the fall.…”
Section: Resultsmentioning
confidence: 96%
“…É fracamente adsorvido pelos coloides do solo, apresentando coeficiente de partição (Kd) entre 0,22 e 0,59 L kg -1 , o que sugere que essa molécula pode mover-se facilmente no perfil do solo (Baskaran & Kennedy, 1999). A meia-vida do pyrithiobacsodium em campo é de 62 dias, e sua atividade residual no solo pode causar injúrias em culturas em sucessão, como soja, trigo e sorgo (Webster & Shaw, 1995). Problemas de carryover relacionados ao pyrithiobac-sodium têm sido observados em solos com elevados teores de argila e baixos valores de pH (Smith et al, 2005).…”
Section: Introductionunclassified